5(n+3)=3(1-n-1)

Simple and best practice solution for 5(n+3)=3(1-n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(n+3)=3(1-n-1) equation:


Simplifying
5(n + 3) = 3(1 + -1n + -1)

Reorder the terms:
5(3 + n) = 3(1 + -1n + -1)
(3 * 5 + n * 5) = 3(1 + -1n + -1)
(15 + 5n) = 3(1 + -1n + -1)

Reorder the terms:
15 + 5n = 3(1 + -1 + -1n)

Combine like terms: 1 + -1 = 0
15 + 5n = 3(0 + -1n)
15 + 5n = 3(-1n)

Remove parenthesis around (-1n)
15 + 5n = 3 * -1n

Multiply 3 * -1
15 + 5n = -3n

Solving
15 + 5n = -3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3n' to each side of the equation.
15 + 5n + 3n = -3n + 3n

Combine like terms: 5n + 3n = 8n
15 + 8n = -3n + 3n

Combine like terms: -3n + 3n = 0
15 + 8n = 0

Add '-15' to each side of the equation.
15 + -15 + 8n = 0 + -15

Combine like terms: 15 + -15 = 0
0 + 8n = 0 + -15
8n = 0 + -15

Combine like terms: 0 + -15 = -15
8n = -15

Divide each side by '8'.
n = -1.875

Simplifying
n = -1.875

See similar equations:

| 4/5s-3/4s=7/10 | | -3x-4=-9-4x | | 23.1=6.6x | | 17-2(x+3)=9 | | -6x-46=-11x+74 | | (1+2x)/7+(5-x)/3=37/21 | | .11k+1.5=2.4 | | 19.79+0.8-12.3c=-19.71-14.9c | | 5x-6(x+3)=15 | | 3x-7+2x+4-7x= | | -79+x=54+8x | | a/7+5/7+2/7 | | 8b-0.5=9b | | -190-2x=-10x+50 | | y-12=-3 | | Y+2=5y-6 | | 8-9(k-3)=14k-11 | | b/5=19 | | x^2+14x=-20 | | 5x^2=2x-7 | | 4x-5(x+3)=16 | | 4+x=-13 | | 5x+21=2x+15 | | -2.86-17.1t=5.24-15.3t | | 5x+6=x+22 | | 1/3(2x+4)+5=-2/3(x+1) | | 6.25x+12=30.75 | | 2/3(4x-10) | | 9v-6=5v+18 | | (6x+15)/4=-15x-25+(5/4) | | 8-9(3-k)=14k-11 | | 10[3p+4]-1=49 |

Equations solver categories